Mapping the current trends and hotspots of adult hippocampal neurogenesis from 2004–2023: a bibliometric analysis - Liu, Ye; Zhang, Jian; Gu, Xiyao; Jia, Shushan (Frontiers in Neuroscience, 2024)
Objective We utilized bibliometric and data visualization techniques to discern the primary research domains and emerging frontiers in the field of adult hippocampal neurogenesis (AHN). Methods We systematically searched the Web of Science database for AHN-related articles published between 2004 and 2023. The retrieved articles were filtered based on publication types (articles and reviews) and language (English). We employed CiteSpace, VOSviewer, and the online bibliometric platform (bibliometric.com) to visualize and analyze the collected data. Results In total, 1,590 AHN-related publications were discovered, exhibiting a steady increase in yearly publications over time. The United States emerged as the leading contributor in AHN research in terms of both publication quantity and national influence. Among all research institutions in the field of AHN, the University of California System exhibited the highest impact. Kempermann, Gerd was the most active author. The publications of the top three active authors primarily focused on the functions of AHN, and reversing hippocampal damage and cognitive impairment by improving AHN. An analysis of reference co-citation clustering revealed 8 distinct research clusters, and the notable ones included “adult hippocampal neurogenesis,” “neurogenesis,” “hippocampus,” “dentate gyrus,” “neural stem cell,” and “depression.” Additionally, a burst keyword detection indicated that ‘anxiety’ is a current research hotspot in the field of AHN. Conclusion This in-depth bibliographic assessment of AHN offers a deeper insight into the present research hotspots in the field. The association between AHN and cognitive diseases, such as Alzheimer’s disease (AD) and anxiety, has emerged as a prominent research hotspot.